PENGENDALIAN KUALITAS PRODUK PIPA PADA PUMP IN ROLL DI PT. XYZ DENGAN MENGGUNAKAN METODE SIX SIGMA - Putu Wiyoga Fernandha Y; Ahmad; Doaly, Carla Olivia (Jurnal Mitra Teknik Industri, 2024)
The rapid development of the industry today has made the level of competition between companies even stronger. Companies are increasingly fighting over consumers and trying to make their products more superior and desirable. Competition between companies cannot be avoided, thus companies must pay attention to several things during the production process so that they can facethe tough competition, one of which is to pay more attention to the quality of the products that will be marketed to consumers and minimize production defects so that consumer satisfaction can be fulfilled. In the interviews conducted, several product defects were obtained in the form of corrugated welding results of 54.35%, jagged cuts of 10.87%, sanding left 26.09% of residual welds and the result of painting on the pipe was lumpy of 8.70%. There are root problems in the production of pump in roll pipes, namely the human operator fatigue factor, the machine factor because there is no routine maintenance on the welding machine so that the welding process is not optimal, the method factor is the absence of WPS (welding process certification) in the welding work area and on environmental factors because there is no protection in the welding process area to avoid dust and water during the welding process. These factors have an impact on the pump in roll pipe production process so that it experiences several types of defects such as corrugated welding, jagged cutting processes, sanding which still leaves residual welds and lumpy and scratched paintwork.